Herb powiatu zduńskowolskiego - Adamczewski, Marek (Biuletyn Szadkowski, 2014)
The County Council in Zduńska Wola made a resolution on 24th November 2000 to adopt a county coat of arms. It features St. Maksymilian M. Kolbe, a monk and martyr. The Saint's ties with Zduńska Wola influenced the direction of search for a symbolic reference for Zduńska Wola county arms. St. Maksymilian M. Kolbe (bom in Zduńska Wola in 1894) is the patron of Zduńska Wola, and 10th October - the day of his canonisation - is the Feast of Zduńska Wola. Memory of the Saint's links with his place of birth is cultivated by the Museum - home of St. Maksymilian M. Kolbe in Zduńska Wola, set up in 1994, on the centenary of his birth. In 2004 the church of the Assumption of Virgin Mary in Zduńska Wola was named the Sanctuary of the Birth and Baptism of St. Maksymilian M. Kolbe. Zduńska Wola county coat of arms received a positive opinion from the administration minister. The only objection that could be raised by a heraldist may concern the too realistic (non-heraldic) presentation of the figure of St. Maksymilian M. Kolbe.